PEMANFANTAN CAIRAN INFUS SEBAGAI PENGGANTI REAGEN ALTERNATIF HAYEM DALAM PEMERIKSAAN HITUNG JUMLAH ERITROSIT - Ahmad Jazuly Nabil; Ariska Widya; Nastasya Nunki; Gilang Nugraha (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2020)
Anemiasufferers in Indonesia are increasing. Anemia diagnosisconfirmed by examining red blood cell (RBC) which requires Hayem as reagent. Problemof running out reagents still widely found that distrupts health services.0.9% infusion fluid is physiological solution and readily available. Therefore, this study aims to ultilize 0.9% intravenous fluids as alternative to Hayem in RBC examination by analyzing differences in results of alternative reagents to Hayem reagent. This type of research is experimental, using normality test, t-test, and linear regression.Carried out in the hematology laboratory of Nahdlatul Ulama University Surabaya in February 2020.Use 25 samples from students and health faculty staff with average infusion fluid ie 4,54 x 106 /µL (SD 0,59 x 106 /µL) while Hayem reagent ie 4,63 x 106 /µL (SD 0,52 x 106 /µL)and there is no difference two results (P = 0.197). fluid normality test was obtained Sig.= 0,716, while Hayem reagent Sig.= 0,923. Paired sample t-test obtained Sig.= 0,197. Resultsof linear regression test showed correlation coefficient of 0.823 and coefficient determination of 67.8% (P = 0.000) with equation Y = 0.725X + 1.339. It was concluded that 0.9% infusion fluid could be used as alternative reagent for Hayem in RBC examination.